Analyze & Classify Intrusions to Detect Selective Measures to Optimize Intrusions in Virtual Network (International Journal of Engineering and Computer Science, 2014)
Cloud computing provides a rich set of features and facilitate user to install softwares and applications in virtual machine (VM) temporally to finish their task with that software which is required and not available in cloud. But some attackers mislead this feature to introduce vulnerability as applications into VM. These applications are distributed over the virtual network and denial some services running over the VM accessing unknowingly by multiple users. To prevent vulnerabilities in VM we are introducing a network agent periodically scans the VM for vulnerable things and reported to attack analyse. It build attack graph by analyse the attack to know its type and apply selective measures to optimize it by network controller with help of VM Profiler.